The Dynamic Interplay Between Employees' Feedback-Seeking Strategies and Supervisors' Delivery of Performance Feedback - Larson, James R. (Academy of Management Review, 1989)
James R. Larson, Jr., The Dynamic Interplay between Employees' Feedback-Seeking Strategies and Supervisors' Delivery of Performance Feedback, The Academy of Management Review, Vol. 14, No. 3 (Jul., 1989), pp. 408-422